Análisis del impacto del incremento de los precios de los fertilizantes en los costos de producción y los precios de venta de maíz amarillo duro en la provincia de los Ríos durante el período de 2010 a 2013 - Lara Brito, Marco Vinicio (2014)
The yellow corn is one of the most important products in the Ecuadorian agricultural sector and is part of the productive chain of chicken and pork, this crop is sown in several provinces of the Ecuadorian coast, however where there is the highest concentration this crop is in the province of Los Rios. In the present investigation was conducted a study to determine the structure of production costs for yellow corn in the province of Los Rios, in their different ways of planting, with this tool the Ministry of Agriculture, Livestock, Aquaculture and Fisheries may determine ease the minimum support price of the product that is done every planting season in winter and summer ..